A Novel Nonsense Mutation Associated with an Exon Skipping in a Patient with Hereditary Protein S Deficiency Type I - Okamoto, Yoshihiro; Yamazaki, Tomio; Katsumi, Akira; Kojima, Tetsuhito; Takamatsu, Junki; Nishida, Mikio; Saito, Hidehiko (Thrombosis and Haemostasis, 1996)
The genetic defect in a patient with hereditary type I protein S (PS) deficiency was investigated. All the exons and intron-exon junctions of the patient’s PS gene were amplified by PCR and subjected to heteroduplex screening. Only the PCR product of exon 4 revealed heteroduplex bands. A novel nonsense mutation, Ser62 (TCA) to Stop (TGA) was found in exon 4. RT-PCR detected the aberrant mRNA in the patient’s platelets, which was markedly reduced in amount and lacked the region of exon 4, suggesting that the nonsense mutation affected the mutated mRNA metabolism and induced exon skipping. The skipping of exon 4 causes an in-frame deletion of 29 amino acids which just construct the thrombin-sensitive region of the PS molecule. The loss of such an important domain as well as the quantitative decrease in the mutated mRNA appear to be responsible for the type I PS deficiency in this patient.